Programming logic and design : comprehensive - Joyce Farrell (Course Technology, 2007)
1. An overview of computers and logic -- 2. Understanding structure -- 3. Modules, hierarchy charts, and documentation -- 4. Desiging and writing a complete program -- 5. Making decisions -- 6. Looping -- 7. Control breaks -- 8. Arrays -- 9. Advanced array manipulation -- 10. Using menus and validating input -- 11. Sequential file merging, matching, and updating -- 12. Advanced modularization techniques -- 13. Object-oriented programming -- 14. Event-driven programming with graphical user interfaces -- 15. System modeling with UML -- 16. Using relational databases -- Appendix A. Solving difficult structuring problems -- Appendix B. Understanding numbering systems and computer codes -- Appendix C. Using a large decision table -- Glossary -- Index